1985
DOI: 10.1128/jcm.22.4.587-589.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sedimentation and flotation techniques for identification of Cryptosporidium sp. oocysts in a large outbreak of human diarrhea

Abstract: Cryptosporidiosis, previously seen mostly among immunocompromised patients, is now recognized among immunocompetent patients. During a large outbreak of cryptosporidiosis in two day-care centers, we compared two procedures for the demonstration of the organism in preserved stool specimens. Of 703 stool specimens tested by both techniques, Sheather sucrose flotation (SSF) identified 127 (18.1%) as positive for Cryptosporidium sp. oocysts. Ritchie Formalin-ethyl acetate sedimentation (F/EA) plus a modified cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 15 publications
1
22
0
2
Order By: Relevance
“…In one study in Bangkok, polymicrobial infections were not found more frequently with Cryptosporidium than with other gastrointestinal pathogens (255). Although some have suggested that a significant association exists between Giardia lamblia and Cryptosporidium (136,300), others have disagreed (121,174), and such a synergistic association is not supported by the composite survey studies (from references in Table 4).…”
Section: Infection In Humansmentioning
confidence: 98%
See 1 more Smart Citation
“…In one study in Bangkok, polymicrobial infections were not found more frequently with Cryptosporidium than with other gastrointestinal pathogens (255). Although some have suggested that a significant association exists between Giardia lamblia and Cryptosporidium (136,300), others have disagreed (121,174), and such a synergistic association is not supported by the composite survey studies (from references in Table 4).…”
Section: Infection In Humansmentioning
confidence: 98%
“…Stool concentration techniques include flotation in Sheather sucrose solution, in zinc sulfate (33% to saturated), or in sodium chloride (36% to saturated) or sedimentation with Formalin ether (modified Ritchie) or Formalin ethyl acetate. One comparison of four techniques found no appreciable difference among methods (6), while another found Formalin ether to be the most sensitive for sedimentation and sodium chloride the most sensitive for flotation (56); others have found Sheather sucrose as or more effective than Formalin ether or Formalin ethyl acetate (161,174,308). Sheather solution allows immediate recognition of pink-tinged oocysts by using high-power magnification, but oocysts begin to disrupt and lose their characteristic spherical shape after as little as 15 min (161,174,308); furthermore, they may not adhere to glass slides for permanent record and staining may be altered.…”
Section: Diagnosismentioning
confidence: 99%
“…Moreover, the sugar flotation technique is more cumbersome to perform, and the presence of the sugar solution of Sheather"s (Sheather"set al, 1923) could inhibit staining procedures (Casemoreet al, 1985). Similarly, epidemiological data did not support the superiority of Sheather's sugar flotation for the detection of Cryptosporidium oocysts in stool specimens (McNabb et al, 1985). Recently, the use of several copro-antigen tests or antigen detection assays have been employed as another diagnostic modality in detecting Cryptosporidium antigens in stool samples (Jexet al, 2008).…”
Section: IVmentioning
confidence: 99%
“…Some workers have found no differences among these methods, whereas others have found the formalin-ether and sodium chloride flotations to be the most sensitive (5, 53,112). Some researchers think that the Sheather's sugar solution gives results equal to or better than those obtained with formalin-ether or formalin-ethyl acetate (88,213,357). When Sheather's sugar solution is used, oocysts appear pink-tinged by bright-field microscopy (Fig.…”
Section: Figmentioning
confidence: 99%